The Use of Local Breed for Milk Production in Indonesia - I Ketut Sutama (Indonesian Center for Animal Research and Development, 2008)
Buffalo (river and swamp), Hissar cattle and Etawah grade (PE) goats are three breeds of potential livestock which can be developed as dairy animals in Indonesia to increase national milk production. Riverine buffaloes (Murrah) are found only in North Sumatera province. Hissar cattle are found in a relatively small number in Sumbawa, West Nusa Tenggara and North Sumatera provinces. Swamp buffaloes and PE goats are mostly found in Java. Under traditional management system in Indonesia, potential milk production of buffaloes varied 0.5 – 2.25 l/day, while Hissar dan PE goats produced milk of 2 – 5 l/day and 0.5 – 2 l/day, respectively. These animals are well adapted with local environmental conditions, hence, become their biological strengths. In some areas, the farmers are familiar in rearing these animals, so that development of buffalo, Hissar and PE production will be easier to be implemented. It is still required to disseminate the relevant information in order to support the improvement of people nutritional status and increase farmers’ income. Key words: Buffalo, Hissar, PE goat, milk